Enhancement factors of sers substrates based on monometallic and bimetallic nanoparticles embedded on reduced graphene oxide - Pillai, Nashmitta; Shatar, Liyana; Mustafa, Fatin H.; Aziz, Muhammad S.A.; Alwahib, Ali A.; Kamil, Yasmin M.; Suhailin, Fariza H. (Springer, 2025)
This study presents a comparison of the enhancement factor (EF) of surface enhanced Raman scattering (SERS) substrates based on monometallic gold (Au), silver (Ag) and bimetallic gold-silver (Au-Ag) nanoparticles (NPs) embedded on reduced graphene oxide (rGO). The graphene oxide (GO) was synthesized via a modified Hummer’s method and thermally reduced to form rGO. The NPs (Au, Ag and Au-Ag) were chemically synthesized via a bottom-up method and combined with rGO to form nanocomposites. The Au, Ag and Au–Ag bimetallic NPs exhibited surface plasmon resonance (SPR) peaks at 522, 384 and 415 nm, respectively, reflecting the influence of composition and alloying. Structural and morphological analysis revealed face-centered cubic NPs with lattice fringes and spherical shape, while rGO displayed a wrinkled sheet-like morphology, providing a high surface area for NPs attachment. The SERS performance was evaluated using rhodamine 6G (R6G) as a Raman reporter to calculate the enhancement factor (EF). The bimetallic Au-Ag/rGO substrate exhibited an EF of 1.12 × 108, significantly 4 times higher than Au/rGO (2.70 × 107) and 2 times higher than Ag/rGO (4.92 × 107), with detection limit of R6G as low as 10− 10 M. This enhancement was attributed to the synergistic plasmonic coupling between Au and Ag, which generated stronger localized electromagnetic fields and increased hotspot density. These observations signify the potential of the bimetallic Au-Ag/rGO SERS substrate over the monometallic NPs for practical applications.